The prince of risk - Reich, Christopher, 1961- (Doubleday, 2013)
When his father, a chairman of the New York Stock Exchange, is killed in a brazen attack on the White House lawn, Bobby Astor, a rising hedge fund manager, untangles a web of lies to reveal a sophisticated plot against the U.S. financial system.